Model Pembiasaan dalam Pembentukaan Akhlak Peserta Didik di Sekolah Dasar - Safitri, Melda; Wirdati, Wirdati (ANWARUL, 2023)
The purpose of this study is to discuss the habituation model in the formation of the morals of students in elementary schools. The formation of morals is very important because morals are the main foundation in the formation of the human person. There are many student moral phenomena that are not in accordance with educational goals, so what can be done is to use a habituation model. This study uses a qualitative method with a descriptive approach. Sources were taken from school principals, PAI teachers, and students. To obtain research data, researchers used interview guidelines and observation guidelines as research instruments. The techniques used in research are observation, interviews and documentation. While the technical data analysis used is using data analysis data reduction, data presentation and conclusions. The results showed that the habituation model implemented at SDIT Juara Padang Panjang was in the form of routine activities such as Dhuha, Zuhr and Asr prayers in congregation, sunnah fasting, spontaneous activities such as 5S culture, exemplary behavior, speaking and programmed activities that have been scheduled on the educational calendar.